A Monsoon Low over BoB & Unprecedented Heavy Rainfall over Maharashtra, India: Case Study of July 2021 - Kant, Shashi (Discontinuity, Nonlinearity, and Complexity, 2026)
This paper provides a detailed overview of the meteorological conditions that led to persistent heavy rainfall events and subsequent flooding in parts of Maharashtra during July 20-24, 2021. Meteorological factors such as an off-shore trough, a shear zone, a cyclonic circulation over south Gujarat, and a Low Pressure Area (LPA) over the Northwest Bay of Bengal (BoB) were identified as favorable environmental conditions. The combination of these factors created an environment conducive to persistent heavy rainfall over Maharashtra. The off-shore trough, shear zone, and cyclonic circulation facilitated moisture convergence and uplift, resulting in widespread rainfall. Additionally, the presence of the LPA intensified moisture influx and atmospheric instability, amplified the intensity of the rainfall event. The trough associated with the cyclonic circulation of the LPA acted as a moisture channel, allowing moisture transport from both the Arabian Sea (AS) & BoB to Maharashtra. Favorable dynamical conditions, such as lower level convergence (LLC) and upper level divergence (ULD), further supported persistent heavy rainfall weather events over the region. Understanding these meteorological conditions is essential for forecasting and mitigating the impacts of extreme weather events like heavy rainfall and flooding. Analyzing the atmospheric dynamics and synoptic patterns associated with such events enables meteorologists to enhance early warning systems and provide timely information to help communities prepare for and respond to such situations effectively.